Optimization of Culture Conditions in Production of Chlorella vulgaris Biomass - Kalender, Mehmet; Bürkev, Sümeyye (Kırıkkale Üniversitesi, 2022)
In this work, optimization of microalgal biomass production using C. vulgaris was investigated. The optimization experiments were carried out according to the working table formed by Response Surface Method (RSM). Each experiment was conducted in 250 mL flasks with a?12-hour?periods in the light (3000 lux)/dark?cycle and at 25 °C. The culture volume, the inoculation ratio, and the culture time were selected as the independent variables. The response variable was the algal biomass concentration. The concentration of algal biomass was measured using UV-Visible spectroscopy method. As a result of the optimization studies, it was determined that the best model representing microalgal biomass production is quadratic source. From ANOVA tests for the quadratic model, it was observed that the three independent variables were also important on the model developed. However, it was determined that the inoculation ratio was less effective than other independent variables, and even, the quadratic effect of this parameter was not effective on the model. It was concluded that the most effective independent variable on the model was time. From RSM analyses, it was founded that the binary interaction of the culture volume-the inoculation ratio was effective on the model. The 3D graphs of this binary interaction showed that the algal biomass concentration was high at high inoculation ratio and at low culture volume in the working range. Optimum C. vulgaris biomass production conditions suggested by RSM were determined as 85,693 mL culture volume, 12,152% inoculation ratio, and 16,952 days.

Bu çalışmada, C. vulgaris mikroalgal biyokütle üretiminin optimizasyonu incelenmiştir. Optimizasyon çalışmaları Design Expert programında Cevap Yüzey Metodu (RSM) ile oluşturulan deneysel çalışma tablosuna göre gerçekleştirilmiştir. Her bir deney 250 mL’lik erlenlerde 12 saat aydınlık (3000 lüx) 12 saat karanlık ve 25 °C’de yürütülmüştür. RSM deneylerinde bağımsız değişkenler olarak kültür hacmi, inokülasyon oranı ve kültür süresi; cevap değişkeni olarak ise üretilen algal biyokütle konsantrasyonu seçilmiştir. Algal biyokütle konsantrasyonları UV-Visible spektroskopisi ile ölçülmüştür. Optimizasyon çalışmaları sonucunda mikroalgal biyokütle üretimini en iyi temsil eden modelin kuadratik olduğu belirlenmiştir. Kuadratik model için ANOVA testlerinden geliştirilen model üzerinde çalışılan üç bağımsız değişkenin de önemli olduğu görülmüştür. Bununla beraber, inokülasyon oranının diğer bağımsız değişkenlere göre daha az etkili olduğu, hatta bu parametrenin kuadratik etkisinin model üzerinde etkili olmadığı saptanmıştır. Model üzerinde en etkili bağımsız değişkenin ise süre olduğu sonucuna ulaşılmıştır. RSM analizlerinden model üzerinde kültür hacmi-inokülasyon oranı ikili etkileşiminin önemli olduğu gözlenmiştir. İkili etkileşim grafiğinden çalışılan aralıkta yüksek inokülasyon oranı ve düşük kültür hacmi değerlerinde algal biyokütle konsantrasyonunun yüksek olduğu sonucuna varılmıştır. RSM ile ileri sürülen optimum C. vulgaris biyokütle üretim şartları 85,693 mL kültür hacmi, %12,152 inokülasyon oranı ve 16,952 gün süre olarak belirlenmiştir.
Chlorella vulgaris Biyokütle Üretiminde Kültür Şartlarının Optimizasyonu
Keywords: Engineering; Mühendislik